Nasal Analysis of Classic Animated Movie Villains versus Hero Counterparts - Allen, Meredith A.; Lucas, Jordyn P.; Chung, Michael; Rayess, Hani M.; Zuliani, Giancarlo (Facial Plastic Surgery, 2020)
Opposing facial features between animated villains and heroes have historically been used to demonstrate contrasting morality between characters, and this could have an impact on how humans view someone as good or evil in everyday life. Studies have been done investigating classic dermatologic features of villainous characters. This principle can be applied to nasal features as well. A search for “top animated characters” was performed. Characters were chosen from American Film Institute's “The Top Tens,” Rolling Stone's “25 Best Pixar Movie Characters,” and Screenrant's “The 30 Best Animated Movie Characters of All Time.” Twenty villains and twenty hero counterparts from respective films were chosen. Classic nasal features were analyzed. Twenty villains (14 male, 6 female) and 20 heroes (12 male, 8 female) were analyzed. Sixteen villains (80%) had greater than normal nasal frontal angle versus 18 heroes (90%). Thirteen villains (65%) had an acute nasolabial angle versus two heroes (10%). Two villains (10%) had excess columellar show versus seven heroes (35%). Seven villains (35%) and one hero (5%) had a dorsal hump. Twelve villains (60%) had an overprojected chin versus three heroes (15%). Villains in pre-2000s films more frequently had a dorsal hump, overprojected chin, ptotic tip, pollybeak deformity, and bulbous tip. Heroes in pre-2000s films more frequently had an overrotated tip. Villains and heroes commonly have a greater than normal nasofrontal angle. Villains more commonly have an acute nasolabial angle, underrotated tip, overprojected chin, dorsal hump, and pollybeak deformity. Heroes more commonly have a large nasolabial angle and overrotated tip. Further research in conjunction with psychologists is required to obtain concrete data on how this affects whether an individual in real life is seen as good or evil, and the impact this has on interactions in society, including in the medical field.
Keywords: nasal analysis; nasal characteristics; animated characters; character design